1993
DOI: 10.1021/jf00026a001
|View full text |Cite
|
Sign up to set email alerts
|

Potential anticarcinogenic natural products isolated from lemongrass oil and galanga root oil

Abstract: Guided by the glutathione S-transferase (GST) assay, fractionation of lemongrass oil and galanga root oil from the plants Cymbopogon citratus and Alpinia galanga , respectively, led to the isolation of four active compounds: d-limonene (1) and geraniol (2) from lemongrass oil; ethyl trons-cinnamate (3) and ethyl 4-methoxy-trons-cinnamate (4) from galanga root oil. Their structures were determined on the basis of spectral analysis. These compounds were tested for their capacity to induce the activity of the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…In addition to this moderate cytotoxicity, /3-caryophyllene has recently been reported to show glutathione S-transferaseinducing activity (13) which is believed to play a role in carcinogen detoxification (14). Importantly, this sesquiterpene hydrocarbon is identified in many edible plants, food spices, beverages, and is frequently used for fragrance and flavor (15).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this moderate cytotoxicity, /3-caryophyllene has recently been reported to show glutathione S-transferaseinducing activity (13) which is believed to play a role in carcinogen detoxification (14). Importantly, this sesquiterpene hydrocarbon is identified in many edible plants, food spices, beverages, and is frequently used for fragrance and flavor (15).…”
Section: Resultsmentioning
confidence: 99%
“…Ethylp-methoxy cinnamate has been reported as the major constituent of rhizome oil of K. galanga of different origins (Tewtrakul et al 2005;Sukari et al 2008). This component has been reported to show many biological activities, such as anti-cancer (Zheng et al 1993) and anti-monoamine oxidase activities (Noro et al 1983). Our report is in agreement with Puthan et al (1926) and Sudibyo (2000) who reported that the oil of K. galanga possessed ethyl cinnamate and ethyl-p-methoxy cinnamate as the main components, which is contrary to the the report of Tewtrakul et al (2005) who reported methyl cinnamate and ethyl-pmethopxy cinnamate as major constituents.…”
Section: Molecular Profiling Of In Vitro Conserved Somaclonesmentioning
confidence: 99%
“…The ethanol extract of A. katsumadai also showed anti-inflammatory potential (Choi et al, 2009;Yang et al, 2009), and two flavonoids derived from the herb exhibited potent cytotoxic effect against tumor cells (Hahm et al, 2003;Hua et al, 2009). An 80% aqueous acetone extract from the rhizomes of A. galanga showed NO production inhibitory activity in mouse peritoneal macrophages (Morikawa et al, 2005), while ethyl 4-methoxy-trans-cinnamate and 1 S-1 -acetoxychavicol acetate from the herb, respectively, exhibited anti-carcinogenic effects (Zheng et al, 1993) and anti-inflammatory effects (Ando et al, 2005). Anti-cancer or anti-inflammatory effects are reported from A. blepharocalyx (K.) (Ali et al, 2001a,b;Kadota et al, 2003;Tezuka et al, 2001), A. calcarata Rosc.…”
Section: Discussionmentioning
confidence: 99%